The empathy and stress mindset of healthcare workers: the chain mediating roles of self-disclosure and social support - Wu, Jinxia; Dou, Jinhua; Wang, Daofeng; Wang, Lizhuo; Chen, Feng; Lu, Guohua; Sun, Lin; Liu, Jianlan (Frontiers in Psychiatry, 2024)
The hospital is a workplace full of stressful events for healthcare workers (HCWs) due to unpredictable changes in their daily routines. Perceptions of stressful events (stress mindset) have a significant impact on an individual's health and well-being. However, few studies have reported the factors and potential counter mechanisms influencing these perceptions. This study aimed to evaluate the relationship between empathy, self-disclosure, social support, and stress mindset of HCWs, and to explore the mechanism of empathy on stress mindset. Five hundred and eight HCWs (35.2% men and 64.8% women) completed the Interpersonal Reactivity Index (IRI), the Distress Disclosure Index (DDI), the Social Support Rating Scale (SSRS), the Stress Mindset Measure (SMM), and demographic questionnaires online in China. The results showed that empathy was positively linked with stress mindset and positively correlated with self-disclosure and social support. In the multiple mediating model, self-disclosure and social support mediated the association between empathy and stress mindset sequentially. The results imply that empathy, self-disclosure, and social support play a significant role in the formation of HCWs' stress mindset. These findings have substantial ramifications for reducing stress and creating successful government interventions to fortify stress mindset in healthcare.